Automated survey of 8000 plan checks at eight facilities. Issue 9 (4th August 2016) - Halabi, Tarek; Lu, Hsiao‐Ming; Bernard, Damian A.; Chu, James C. H.; Kirk, Michael C.; Hamilton, Russell J.; Lei, Yu; Driewer, Joseph
Abstract : Purpose: To identify policy and system related weaknesses in treatment planning and plan check work‐flows. Methods: The authors' web deployed plan check automation solution, PlanCheck, which works with all major planning and record and verify systems (demonstrated here formosaiq only), allows them to compute violation rates for a large number of plan checks across many facilities without requiring the manual data entry involved with incident filings. Workflows and failure modes are heavily influenced by the type of record and verify system used. Rather than tackle multiple record and verify systems at once, the authors restricted the present survey tomosaiq facilities. Violations were investigated by sending inquiries to physicists running the program. Results: Frequent violations included inadequate tracking in the record and verify system of total and prescription doses. Infrequent violations included incorrect setting of patient orientation in the record and verify system. Peaks in the distribution, over facilities, of violation frequencies pointed to suboptimal policies at some of these facilities. Correspondence with physicists often revealed incomplete knowledge of settings at their facility necessary to perform thorough plan checks. Conclusions: The survey leads to the identification of specific and important policy and system deficiencies that include: suboptimal timing of initial plan checks, lack of communication or agreement on conventions surrounding prescription definitions, and lack of automation in the transfer of some parameters.